Perceraian Orang Tua dan Sikap Introvert Anak - Yunita Sri Wulandari, Kristina; purnamasari, Rita; awlia, Winda (Jurnal Educazione : Jurnal Pendidikan, Pembelajaran dan Bimbingan dan konseling, 2023)
A child is a gift from Allah SWT. Who has the right to life and get attention from both parents. How parents educate and raise them greatly influences the development of a child. A child is likened to a clean white paper which is given a potential by Allah SWT, and must be developed by every parent in any situation, such as in a problem caused by the separation of the marriage bond of both parents. Introversion is an obstacle or obstacle in interpersonal conversation, which has the characteristics of a cognitive association that is closed by beliefs and disbelief about reality and is closed, feels alone, sensitive, adjusts to the world outside itself that is not good, difficult to get along with and less able to attract the hearts of others. Separation of parents is a big enough problem for a child, especially for children who are still at an early age, because children at this age still really need attention from both parents.